The effectiveness of leadership and organizational culture in Batusangkar on the management of micro, small, and medium enterprises - Fitri, Sri Adella; Ramadanis; Marlin, Khairul; Rahmi, Mega; Fitria, Nita (The Economics and Finance Letters, 2025)
The purpose of the study was to evaluate the influence of leadership and organizational culture on the success of MSMEs in Batusangkar. The research approach was quantitative. The sample consisted of 267 MSME entrepreneurs in Batusangkar. Data collection techniques used questionnaires and documentation. Data analysis techniques included descriptive statistics and logistic regression analysis to explore the relationship between variables with the help of SPSS Version 29.0. The results found that leadership and organizational culture partially have a significant and positive influence on the success of MSME management in Batusangkar. Effective leadership provides direction and motivation, thus creating a productive work environment. It was also found that organizational culture encourages collaboration and open communication between MSME business actors. It was also found that leadership and organizational culture simultaneously have a positive and significant impact on management success. The conclusion is that the implementation of effective leadership practices and the development of a strong organizational culture are fundamental in ensuring economic growth and the most effective way to reduce poverty in Batusangkar. Practical implications are that the implementation of leadership with the development of culture in Batusangkar is used to improve the 21st-century economy.